(untitled) (Scientific journal of the Fergana State University, 2025)
Examples of literary art with wandering plots, widespread among various peoples, as well as works that arose as a result of literary influence, are not only a unique historical source of their time, but also a vivid expression of the literary and aesthetic potential and spiritual and moral views of representatives of a certain people. The plot of the story about Yusuf is considered such a literary phenomenon that has spread all over the world. This problem is discussed in detail in the article.